Craniosynostosis associated with FGFR3 pro250arg mutation results in a range of clinical presentations including unisutural sporadic craniosynostosis. Issue 8 (August 1997) - Reardon, W; Wilkes, D; Rutland, P; Pulleyn, L J; Malcolm, S; Dean, J C; Evans, R D; Jones, B M; Hayward, R; Hall, C M; Nevin, N C; Baraister, M; et al.
Abstract : Several mutations involving the fibroblast growth factor receptor (FGFR) gene family have been identified in association with phenotypically distinct forms of craniosynostosis. One such point mutation, resulting in the substitution of proline by arginine in a critical region of the linker region between the first and second immunoglobulin-like domains, is associated with highly specific phenotypic consequences in that mutation at this point in FGFR1 results in Pfeiffer syndrome and analogous mutation in FGFR2 results in Apert syndrome. We now show that a much more variable clinical presentation accompanies analogous mutation in the FGFR3 gene. Specifically, mental retardation, apparently unrelated to the management of the craniosynostosis, appears to be a variable clinical consequence of this FGFR3 mutation.